(untitled) (Asian Journal of Medical and Biological Research, 2021)
Shrimps are good source of protein and also good exportable item for its quality all over the world. Inappropriate use of antibiotics in the production of local and export quality shrimps can facilitate infiltration of antibiotic residues into human bodies which are toxic enough to cause serious health hazard. The present study was investigated to determine the antibiotic residues in some selected local market and export quality shrimps and also commercial shrimp feeds in chattogram. Local grade and export grade samples of Black tiger shrimps (Penaeus monodon) and feeds of four different companies were taken for the completion of this study. The permissible residual limit for the shrimp samples were- 0.3(μg/kg) for Chloramphenicol and 1.0 (μg/kg) for AHD, AMOZ, SEM, AOZ. Black tiger shrimps from local market 1 had high concentration of Chloramphenicol (0.35 μg/kg) and SEM (1.2 μg/kg) residues whereas Market 2 showed maximum residues in AMOZ (1.2 μg/kg) and SEM (1.1 μg/kg). Whereas, Market 3 showed negative result. Local market 4 had high concentration of Chloramphenicol (0.4 μg/kg) and AOZ (1.2 μg/kg) residues. However, in export grade shrimps antibiotic residues was found under the maximum residual limit in all samples. Also, among four feed tested, two of them were found positive for chlorampenicol and nitrofurans. The result was considered significant where P>0.05. So, legal actions should be taken against the farmers and the farms that overuse antibiotics in shrimps. Also, people should be made aware of the harmful effects of antibiotics so that the impact can be minimized. Asian J. Med. Biol. Res. December 2020, 6(4): 623-627